-4k+3=11

Simple and best practice solution for -4k+3=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4k+3=11 equation:


Simplifying
-4k + 3 = 11

Reorder the terms:
3 + -4k = 11

Solving
3 + -4k = 11

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -4k = 11 + -3

Combine like terms: 3 + -3 = 0
0 + -4k = 11 + -3
-4k = 11 + -3

Combine like terms: 11 + -3 = 8
-4k = 8

Divide each side by '-4'.
k = -2

Simplifying
k = -2

See similar equations:

| -(4+12x)=32 | | 100=2(3.14)r | | 75=19 | | 6+8q=11x+7q | | x^2-40x+3200=0 | | -4+3=11 | | 4-3x=x-6 | | 6(8+x)-6x=8(x+5) | | 2x^2+12=-5x | | 0.30(x+10)+0.30x=12 | | 2(x+7)=5x-35 | | 5x-2=150 | | 100+20= | | -9i(7i-2)= | | 4x+6-2x+6= | | 12=-c+-1.5 | | -18+1p=-16 | | 25-40x=-.49x^2 | | 4x-4=127 | | f(n)=f(n-1)+18 | | 60p-30p=300 | | 3-(-6-9i)-(-7+2i)= | | 12x=6x-48 | | 3=-(-6-9i)-(-7+2i) | | 13=6x+4 | | 2+5y=4 | | -18=y-22 | | -x^2+29x-54=0 | | x+.15x+2.4=2(x-1.3) | | 1+5y=4 | | 25a+125=28a | | T-17.9=-31.05 |

Equations solver categories